Gingival overgrowth during hypertension therapy. A case report and literature review - Wojda, Martyna; Świstowska, Magdalena; Wielgosz, Aleksandra; Mincewicz, Aleksandra; Wach, Damian; Iwaniuk, Kaja; Daniluk, Aleksander (Quality in Sport, 2024)
Introduction and purpose: Hypertension is a global public health issue, affecting over 1.4 billion people and is responsible for a significant portion of deaths due to heart disease and strokes. Pharmacotherapy, especially antihypertensive drugs, can lead to undesirable effects, including gingival overgrowth, which is a known drug-dependent phenomenon. Despite the availability of numerous drugs from various pharmaceutical classes, gingival overgrowth still remains a serious health problem, particularly among older patients. State of knowledge: Drugs such as calcium channel blockers are commonly used in the treatment of hypertension. Amlodipine, a popular calcium channel blocker, is associated with gingival overgrowth, although the incidence of this effect can vary depending on the dose and duration of use. Gingival overgrowth may have multifactorial mechanisms, including drug-cell interactions and the patient’s genetic predispositions. Summary: Drug-induced gingival overgrowth, including amlodipine, is a rare but significant phenomenon that can complicate treatment and lead to serious consequences for the patient. Implementing prophylactic measures, monitoring periodontal state, and continuing periodontal therapy are crucial to minimalize the risk of DIGO. In cases of intensification of symptoms, surgical intervention may be necessary, however, prognosis depends on individual factors, and recurrence can be an issue for susceptible patients.